Relationship between job stressors and organizational change among academic staff at Universiti Teknologi Mara (UiTM) Cawangan Kelantan / Nik Mohd Faris Nik Min …[et al.] - Nik Min, Nik Mohd Faris; Mohd Firdaus Kozako, Intan Nurul ‘Ain; Ishak, Muhammad Ammar Haidar; Abdul Wahab, Mohd Hafeez Al-Amin; Abdullah Thani, Ayu Kamareenna; Sakarji, Siti Rosnita; Aminuddin, Azwan Shah; Badri, Adlie Hakimie (Universiti Teknologi MARA, 2021)
Change usually occurs when an organization replaces its management, technological change or product diversification, et cetera. However, organizational change can increase work stress levels, and employees need to cope with new and old stressors. This research emphasizes the factors of job stressors, such as role overload, role ambiguity, unprofitability, poor peer-relation, and strenuous working conditions. The purpose of this research was to identify the relationship between job stressors and organizational change among academic staff at Universiti Teknologi MARA (UiTM) Cawangan Kelantan (Machang Campus) and to identify the most affected job stressor during the organizational change. The research was non-experimental which was categorized by correlation. Quantitative data was collected using a questionnaire contained three separate sections and was distributed to 155 academic staff at UiTM Cawangan Kelantan (Machang Campus). The reliability analysis was conducted and the Cronbach Alpha value ranged from 0.529 to 0.852. Pearson Correlation was used to examine the relationship between job stressors and organizational change, and it was found that all variables of job stressors had a significant relationship with organizational change except for unprofitability. It was also found that the most affected job Nik Mohd Faris et al./ Advances in Business Research International Journal, 7(1) 2021, 201 - 215 202 stressor during organizational change was poor peer-relation. The researchers hope that this study would educate employees regarding factors affecting job stressors towards organizational change.